A prospective study of filgrastim pharmacokinetics in morbidly obese patients compared with non‐obese controls. Issue 1 (22nd November 2021) - Stewart, Aaron W.; Shillingburg, Alexandra; Petros, William; Wen, Sijin; Piktel, Debra; Moses, Rebecca; Gibson, Laura F.; Craig, Michael; Cumpston, Aaron
Abstract: Introduction: Filgrastim is a human granulocyte colony‐stimulating factor (G‐CSF). There are limited data on dosing filgrastim in obesity. The objective of this study was to compare filgrastim pharmacokinetic parameters for morbidly obese and non‐obese patients after a single subcutaneous dose of filgrastim dosed per actual body weight. Methods: This prospective, matched‐pair study (NCT01719432) included patients ≥18 years of age, receiving filgrastim at 5 μg/kg with a weight >190% of their ideal body weight (IBW) for "morbidly obese" patients or within 80%–124% of IBW for matched‐control patients. The control group was prospectively matched for age (within 10 years), degree of neutropenia, and gender. Filgrastim doses were not rounded to vial size, to allow more accurate assessment of exposure. Blood samples were collected at 0 (prior to dose), 2, 4, 6, 8, 12, and 24 h after the first subcutaneous administration of filgrastim. Results: A total of 30 patients were enrolled in this prospective pharmacokinetic study, with 15 patients assigned to each arm. Non‐compartmental analysis showed that the systemic clearance (Cl) was 0.111 ± 0.041 ml/min in the morbidly obese group versus 0.124 ± 0.045 ml/min in the non‐obese group ( p = 0.44). Additionally, the mean area under the curve (AUC0‐24h ) was 49.3 ± 13.9 ng/ml × min in the morbidly obese group versus 46.3 ± 16.8 ng/mL x min in the non‐obese group ( p = 0.6). No differences were seen in maximum concentrations (Cmax ) between the two groups (morbidly obese: 48.1 ± 14.7 ng/ml vs. non‐obese: 49.2 ± 20.7 ng/ml ( p = 0.87)). The morbidly obese group had a numerically higher, but not statistically significant, increase in time to maximum concentration (Tmax ) compared to the non‐obese group (544 ± 145 min vs 436 ± 156 min ( p = 0.06), respectively). Conclusion: Calculating subcutaneous filgrastim doses using actual body weight appears to produce similar systemic exposure in morbidly obese and non‐obese patients with severe neutropenia.